Exploring the Talaqqi Method in Developing the Ability to Memorize the Qur'an in Children Aged 5-6 Years: A Case Study of Madrasah Manbaul Uloom Malaysia - Danang Prastyo; Ardhana Reswari; Selfi Lailiyatul Iftitah (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2025)
Early childhood Quran memorization has become a rapidly growing tradition in Islamic education in various countries. The talaqqi method as a face-to-face learning approach has been practiced since the time of the Prophet Muhammad, but specific adaptations for children aged 5-6 years have not been explored in depth. Children in the golden age phase have optimal memory capacity but limited attention spans, so the conventional talaqqi method requires modification in accordance with their cognitive development characteristics. The literature gap indicates the need for qualitative research on the pedagogical mechanisms of the talaqqi method adapted to the developmental characteristics of early childhood. This study explores the practice of the talaqqi method in developing the ability of 5-6-year-old children to memorize the Quran, focusing on the adaptation of instructional techniques, structured repetition strategies, and the role of parental involvement. A qualitative case study was conducted at Madrasah Manbaul Uloom Malaysia for four months (June-September 2025), involving 15 children aged 5-6 years, five tahfiz teachers, and ten parents through participant observation, in-depth interviews, focus group discussions, and document analysis. The adaptive talaqqi method optimizes memorization through three pedagogical mechanisms: teacher-student interaction creates accurate articulation modeling while building emotional closeness, segmentation of short verses with structured repetition according to children's working memory capacity, and teacher-parent collaboration creates consistency in the learning environment. Specific instructional techniques include flexible learning duration, the use of Hijaiyah flashcard visual media, a star reward system, and differentiated learning based on the child's individual learning speed. Adapting the talaqqi method based on the cognitive development characteristics of 5-6-year-old children effectively optimizes Al-Quran memorization skills through a developmentally appropriate practice approach. The study recommends implementing a maximum teacher-student ratio of 1:5, a tajwid training program for parents, a formative evaluation system based on differentiation, and a multi-site comparative study to identify variations in the contextual adaptation of the talaqqi method in different countries.